STUDI EKONOMI SYARIAH TENTANG PERUBAHAN PP NO 46 TAHUN 2013 KE PP NO 23 TAHUN 2018 - Mawadah, Sokhikhatul (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2019)
Micro, Small and Medium Enterprises (MSMEs) are one of the drivers of the Indonesian economy. The MSME sector is proven to be able to survive in the midst of the economic crisis in Indonesia. At present, the growth of MSMEs from year to year continues to increase. The more rapid development of MSMEs in Indonesia will cause more contribution to the receipt of the country's Gross Domestic Product. This is where MSMEs become a sector that will have a large potential in the amount of tax revenue. The tax incentive policy for MSMEs previously regulated in Government Regulation Number 46 of 2013 provided that the final tax rate imposed on MSMEs is 1 percent of gross income. However, at present, the regulation has been amended and replaced with Government Regulation Number 23 of 2018, where the final tax rate for MSME players is only 0.5 percent of gross income. If viewed from a sharia economic perspective, a decrease in taxes is a form of government justice for MSME actors, because basically businesses run by MSMEs do not always bring profits, so that a high tax rate can burden them. This is in accordance with the general goal of implementing the economic system, namely to realize prosperity and peace for the entire community. This study aims to provide a critical review of how much the effect of changes in PP on final income tax rates for MSMEs is seen from the literature review involving several Islamic elements. The methodology in this study is qualitative descriptive. Discussion refers to previous research and results from literature studies..